European strategy and legislation for cybersecurity: implications for Portugal - Vidal Carvalho, João (2020)
‘‘Cyber-attacks can be more dangerous than guns and tanks’’. This statement was made by Junker in his speech in the EU ‘‘State of the Union’’ in 2017 and reﬂects the extreme importance of this phenomenon. The increasing variety of devices that can access to Internet has contributed to the overall growth of internet users, in all kinds of places and circumstances. These devices are now part of our lives and we use it for everything. As the number of devices and tasks that we do with it are growing, more prone we are to cyber-attacks. As well, as the number of user’s victim of these attacks are increasing, the general concerns about cybercrime are growing too. The growing list of cybercrimes includes crimes that have been made possible by computers, such as network intrusions and the dissemination of computer viruses, as well as computer-based variations of existing crimes, such as identity theft and terrorism which have become as major problem to people and nations. In this context, the European Union is leading the effort to regulate the defence against cyber-threats in both normative/legal and strategic levels. This reality is also very present in Portugal, where there is a sense of lack of control and capacity to combat this kind of threats. In this article, we present the European Strategy and Legislation for Cybersecurity and how this strategy applies and involves Portugal.